Expert Ministers in New Democracies: Delegation, Communist Legacies, or Technocratic Populism? - Semenova, Elena (2020)
This article examines the appointments and survival of expert ministers (i.e., ministers with educational and professional expertise in the portfolio to which they are appointed) in new democracies. Using a novel data set on 11 Central and Eastern European countries from 1990 until 2012, I test competing hypotheses derived from delegation theory, communist legacies approach, technocratic populism studies, and semi-presidentialism literature. The first study shows that experts without political experience (technocrats) have specific cabinet appointment patterns distinguishing them from party politicians and politically experienced experts. For example, technocrats have high chances of being appointed during an economic downturn. The conditional risk set survival analysis has revealed that compared to their politically experienced colleagues, technocrats have higher chances of remaining in their positions if there was a change in the PM’s candidacy. Moreover, they have long careers independently of the continuity of the PM’s party in government and the PM’s partisan status. Strikingly, patterns of portfolio specialization from the communist period remained in place after the regime change (e.g., expert ministers holding the portfolios of finance and economy). However, holding these specific portfolios does not decrease the minister’s risk of being dismissed. These findings have ramifications for issues surrounding cabinet formation, institutional choice, and populism in new democracies.